Deteksi Gen SLC30A8 pada Sampel Darah Penderita Diabetes Melitus Tipe 2 Dengan Metode Polymerase Chain Reaction - Auliantika, Dinda Helsa; Wahyudi, Didik (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2023)
Background: The SLC30A8 gene is a zinc efflux transporter associated with insulin secretion expressed by the pancreas. The SLC30A8 gene causes abnormalities in insulin synthesis, maturation & secretion as well as abnormalities in the body's effectiveness in responding to glucose metabolism. Polymerase Chain Reaction (PCR) is a DNA amplification method that can be used to detect the presence of the SLC30A8 gene in type 2 diabetes mellitus patients. Methods: This study used a descriptive research method conducted at the Molecular Biology Laboratory of Sekolah Tinggi Ilmu Kesehatan Nasional. The sampling technique in this study used a total sampling technique on 25 type 2 diabetes mellitus patients who were members of the Prolanis Diabetes Mellitus Puskesmas Bulu Sukoharjo, Central Java. The detection of the SLC30A8 gene went through several stages, namely DNA isolation, qualitative testing of DNA isolates, quantitative testing of DNA isolates and PCR Results: The results showed the presence of the SLC30A8 gene in all blood samples from type 2 diabetes mellitus patients using the PCR method. The primer used with forward primer 5'-GGACGAAAGAGTTCCCATAGCG-3' and reverse primer 5'- ATAGCAGCATGTTTTGAAGGTGGC-3' attaches specifically to chromosome 8 with a product length of 429 bp. Conclusion: All blood samples of type 2 diabetes mellitus patients detected the SLC30A8 gene